The Relationship between Physical Activity and Sleep Quality for Class 2020 Students Faculty of Medicine Tarumanagara University - William Widjaya; Susilodinata Halim (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Sleep is one of the basic needs of every human being. Disturbance to the quality of sleep can cause various problems such as a person's disruption in following lessons and low memory. Not only academics will be disrupted, but health will also be disrupted. Someone who has good quality sleep will be more focused on doing something than someone with bad quality. The purpose of this study was to determine whether there is a relationship between physical activity and the quality of sleep of students at the Faculty of Medicine, University of Tarumanagara. This research is a quantitative analytic research with a cross-sectional research design. This research was conducted in Faculty Of Medicine, Tarumanagara University, This research data collection activity took place in January 2022 until completion. The population in this study is all Students of the Faculty Of Medicine, Tarumanagara University. The total sample in this study was 140 people. The sampling method of this study is means of simple random sampling. Data collection in this study used the Global Physical Activity Questionnaire (GPAQ) questionnaire and the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data analysis used with the Chi-Square test. The results of the study showed that there was a significant relationship between physical activity and sleep quality for students of the Faculty of Medicine, Tarumanagara University, class of 2020 (p-value = 0.000; <α 0.005). It is recommended to students of the Faculty of Medicine, Tarumanagara University to improve their health status through diligent regular physical activity and quality sleep in order to increase their level of physical fitness. Oleh Therefore, students need to learn to manage time for academic and non-academic activities, as well as regular breaks and sports.Keywords: Physical Activity, Sleep Quality, Student